SYSTEMIC INFLAMMATORY RESPONSE SYNDROME: THE CURRENT STATUS - Shrestha, Manisha; Kumar, Anand (Journal of Universal College of Medical Sciences, 2018)
Systemic inflammatory response syndrome (SIRS) is a frequent and serious problem faced by clinicians in day to day practice and is a major factor of intensive care morbidity and mortality. The American College of Chest Physicians and the American Society of Critical Care Medicine in 1991 published definitions and criteria for systemic inflammatory response syndrome. Since then many researches have been undertaken to better understand the pathophysiology of systemic inflammatory response syndrome and to determine the accuracy of its diagnostic criteria. The criteria set by the 1991 consensus is still popularly used today. However, with the current knowledge on this matter many researchers have put forward the need of refinement in the criteria of systemic inflammatory response syndrome defined by 1991 consensus. This article aims to review the epidemiology, etiology, pathophysiology, laboratory diagnosis, treatment and the current views regarding SIRS. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 56-61